Pyrexia in pregnancy: an atypical presentation - Deshmukh, Prasad Yeshwant; Patil, Shaifali Kundan; Boricha, B. G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Every year approximately 50 million women living in malaria endemic areas become pregnant and are at high risk of adverse health impact of malaria. Pregnancy appears to interfere with immune process in malaria and the disease itself alters immune reactivity. Malaria is a parasite infestation with protozoan Plasmodium; transmitted through bite of female Anopheline mosquito. We present a case of 25 week multigravida with vivax malaria complaining of breathlessness. On further investigations, patient was found to have bilateral pleural effusion.